Reassessing the Political Leadership of Caliph Uthman bin Affan - Irwan Supriadin (STIT Sunan Giri Bima, 2026)
The leadership of Caliph Uthman ibn Affan was one of the most important and controversial periods in the history of Islamic government. On the one hand, he succeeded in strengthening state administration, expanding the territory of Islamic rule, and codifying the Qur'an through the compilation of the Uthmani Mushaf. On the other hand, the policy of appointing relatives from the Umayyad dynasty to strategic government positions gave rise to accusations of nepotism which later developed into political conflict and culminated in the Great Fitnah . This study aims to analyze the leadership of Caliph Uthman ibn Affan by examining the dynamics of government policies, accusations of nepotism, and the factors behind the political crisis at the end of his caliphate. The study uses a qualitative method with a type of library research through a historical approach and historiographic analysis. Data were obtained from classical Islamic history literature, academic books, and relevant scientific articles, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and drawing conclusions. The research findings show that Uthman's administrative policies were a response to the increasingly complex needs of state governance resulting from the expansion of Islamic territory.